2020
DOI: 10.1186/s40168-020-00813-0
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection exhibits systematic impacts on the drinking water microbiome

Abstract: Limiting microbial growth during drinking water distribution is achieved either by maintaining a disinfectant residual or through nutrient limitation without using a disinfectant. The impact of these contrasting approaches on the drinking water microbiome is not systematically understood. We use genome-resolved metagenomics to compare the structure, metabolic traits, and population genomes of drinking water microbiome samples from bulk drinking water across multiple full-scale disinfected and non-disinfected d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 81 publications
9
114
0
Order By: Relevance
“…For instance, the microbial concentrations in finished drinking water can vary from 10 3 and 10 5 cells/mL 1115 , depending on the presence, absence, and concentrations of the disinfectant residual. Disinfectant residuals not only impact community size, but also impact community structure 3,10,1618 and functional potential 18,19 . Similarly, filtration processes impact downstream microbial communities both by filtration-mediated seeding (Pinto et al ., 2012) and through the biologically mediated removal of nutrients making them unavailable for microbial growth downstream 11,12,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the microbial concentrations in finished drinking water can vary from 10 3 and 10 5 cells/mL 1115 , depending on the presence, absence, and concentrations of the disinfectant residual. Disinfectant residuals not only impact community size, but also impact community structure 3,10,1618 and functional potential 18,19 . Similarly, filtration processes impact downstream microbial communities both by filtration-mediated seeding (Pinto et al ., 2012) and through the biologically mediated removal of nutrients making them unavailable for microbial growth downstream 11,12,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, low DNA concentration or any genetic markers have been demonstrated to give high false-negative results, increased false discovery and artefactual results [44,52] that is likely to be the case for sequencing-based studies in chlorinated drinking water [29]. We found that many reported drinking water microbiome studies from chlorinated systems (including 16s rRNA amplicon sequencing/ metabarcoding, metagenomics) [20,[56][57][58][59][60][61][62][63][64] often exclude raw experimental data of extracted DNA concentrations that is crucial to assess the quality of the sequencing results.…”
Section: No Impact Of Water Volume On Dna Recoverymentioning
confidence: 87%
“…Whereas the focus of this study was solely on the bacterial numbers reached by the innate waterborne community after treatment and how quickly this happened, the composition of the new microbial community is of hygienic relevance. Interestingly, it was recently reported that disinfection exerts a selective pressure on the drinking water microbiome toward microorganisms that can utilize decay products from inactivated biomass (Dai et al 2020).…”
Section: Discussionmentioning
confidence: 99%